Matrix metalloproteinase 10 contributes to hepatocarcinogenesis in a novel crosstalk with the stromal derived factor 1/C‐X‐C chemokine receptor 4 axis. Issue 1 (22nd April 2015) - García‐Irigoyen, Oihane; Latasa, Maria U.; Carotti, Simone; Uriarte, Iker; Elizalde, Maria; Urtasun, Raquel; Vespasiani‐Gentilucci, Umberto; Morini, Sergio; Benito, Patricia; Ladero, Jose M.; Rodriguez, Jose A.; Prieto, Jesus; et al.
Abstract : Matrix metalloproteinases (MMPs) participate in tissue repair after acute injury, but also participate in cancer by promoting a protumorigenic microenvironment. Previously, we reported on a key role for MMP10 in mouse liver regeneration. Herein, we investigated MMP10 expression and function in human hepatocellular carcinoma (HCC) and diethylnitrosamine (DEN)‐induced mouse hepatocarcinogenesis. MMP10 was induced in human and murine HCC tissues and cells. MMP10‐deficient mice showed less HCC incidence, smaller histological lesions, reduced tumor vascularization, and less lung metastases. Importantly, expression of the protumorigenic, C‐X‐C chemokine receptor‐4 (CXCR4), was reduced in DEN‐induced MMP10‐deficient mice livers. Human HCC cells stably expressing MMP10 had increased CXCR4 expression and migratory capacity. Pharmacological inhibition of CXCR4 significantly reduced MMP10‐stimulated HCC cell migration. Furthermore, MMP10 expression in HCC cells was induced by hypoxia and the CXCR4 ligand, stromal‐derived factor‐1 (SDF1), through the extracellular signal‐regulated kinase 1/2 pathway, involving an activator protein 1 site in MMP10 gene promoter. Conclusion : MMP10 contributes to HCC development, participating in tumor angiogenesis, growth, and dissemination. We identified a new reciprocal crosstalk between MMP10 and the CXCR4/SDF1 axis contributing to HCC progression and metastasis. To our knowledge, this is the first report addressing the role of a MMP in hepatocarcinogenesis in the corresponding genetic mouse model. (Hepatology 2015;62:166‐178)